The Relationship Between Parasocial Relationships and Partner Selection Preferences in Early Adult Women K-Pop Fans - Pahlevi, Marwah Reza; Nurdin, Muh. Nur Hidayat; Sulastri, Tri (Polteknik Ilmu Pemasyarakatan, 2024)
In early adulthood, individuals have developmental tasks that must be completed, one of which is choosing a partner. In choosing a partner, individuals have different preferences related to the ideal partner they want. However, many women in early adulthood tend to set high standards for their partners which is the result of parasocial relationships with media figures they idolize. The purpose of this study is to find out the relationship between parasocial relationships and partner selection preferences in early adult women K-Pop fans. The participants in this study are 311 people. The sampling technique used is accidental sampling. The measuring tools used are the multidimensional measure of parasocial relationship scale and the nine mate selection criteria scale. This study uses a pearson product moment analysis technique with a correlation coefficient value of 0.252 and a significance level of p-value <0.001. The results showed that there was a relationship between parasocial relationships and partner selection preferences in early adult women K-Pop fans. In addition, further research is expected to pay attention to other variables that affect partner selection preferences and parasocial relationships but are not researched in this study. The implications of this research can be a source of information in the development of science, especially in the field of social psychology.